DOP45 Adequate infliximab exposure during the induction phase is associated with early complete fistula response in patients with fistulizing Crohn's disease: a post-hoc analysis of the ACCENT-2 trial. (25th January 2019) - Vande Casteele, N; Papamichael, K; Jeyarajah, J; Osterman, M T; Cheifetz, A S
Abstract: Background: Therapeutic drug monitoring is used in clinical practice to optimise infliximab (IFX) therapy in patients with Crohn's disease (CD). However, IFX induction concentration cut-points associated with early post-induction complete response in patients with fistulizing CD are unknown. We aimed to investigate the association of IFX serum concentrations at weeks (W)2, 6, and 14 with complete fistula response assessed at Week 14 (CFR14). Methods: We analysed data from the ACCENT-2 trial, 1 which included 282 patients with active fistulizing CD treated with IFX. In this study, CFR14 was defined as a complete absence of draining fistulas. Receiver-operating characteristic curve analysis was performed to identify IFX concentration cut-points with combined maximal sensitivity and specificity that corresponded to CFR14. A multi-variable logistic regression analysis was performed to evaluate the association of IFX exposure, patient demographics, and disease characteristics with CFR14. Results: In patients who achieved CFR14 compared with those who did not, the median [interquartile range, IQR] IFX concentrations were significantly higher at W6 (18.4 [12.7–27.8] μg/ml vs. 15.2 [9.1–26.0] μg/ml; p = 0.038) and W14 (6.4 [2.3–10.8] μg/ml vs. 3.7 [1.5–7.3] μg/ml; p = 0.001) (Table 1). IFX cut-points of 13.9 μg/ml at W6 and 4.8 μg/ml at W14 were associated with CFR14 (Table 2). Multivariable logistic regression analysis identified W14 IFX concentration as the only independent factor associated with CFR14 with an odds ratio [95% confidence interval] of 1.31 [1.06–1.61]; p = 0.013. Table 1. Serum infliximab concentration by efficacy outcome status. Table 2. Infliximab threshold concentration associated with CFR14. Conclusions: Higher IFX concentrations during induction are associated with early complete fistula response in patients with fistulizing CD. Early accelerated dosing of IFX in a subset of patients with subtherapeutic drug exposure may lead to better outcomes. Reference 1. This study, carried out under YODA Project #, (2017), -1276, used data obtained from the Yale University Open Data Access Project, which has an agreement with Janssen Research & Development, L.L.C. The interpretation and reporting of research using these data are solely the responsibility of the authors, and does not necessarily represent official views of the Yale University Open Data Access Project, or Janssen Research & Development, L.L.C.